Розробка алгоритму моделювання кривих з заданими властивостями - Холодняк, Юлія Володимирівна; Гавриленко, Євген Андрійович; Зінов’єва, Ольга Геннадіївна; Kholodniak, Yuliia; Havrylenko, Yevhen; Zinovieva, Olha (Запоріжжя : 2023, 2023)
UA: Розроблено спосіб, який дозволяє забезпечити неперервний графік швидкості зміни радіусів кривини уздовж обводу. Обвід формується у вигляді кривої, представленої впорядкованою послідовністю точок (дискретно представлена крива). Швидкість зміни радіусів кривини дискретно представленої кривої оцінюється швидкістю зміни радіусів кривини уздовж кривої Безьє, яка визначається відповідним базисним трикутником. Проведено дослідження властивостей кривої Безьє, в результаті яких доведено, що всередині ділянки, вздовж якої значення радіусів кривини змінюються монотонно, значення критерію оцінки швидкості зміни радіусів кривини також змінюються монотонно. Запропоновано критерій оцінки величини розриву швидкості зміни радіусів кривини дискретно представленої кривої. Зменшення розривів значень критерію проводиться в процесі згущень всередині відповідного базисного трикутника, а також всередині попереднього та наступного трикутників. В процесі послідовних згущень максимальна величина розриву значень швидкості зміни радіусів кривини послідовно зменшується. EN: The method that allows to provide a continuous graph of the rate of change of the radiuses of curvature along the contour, is developed in this article. The contour is formed as a curve represented by an ordered set of points (discretely represented curve). In addition to the initial point set, the determinant of the discretely presented curve includes its differential geometric characteristics. These characteristics are provided at the modeling process. The discretely represented curve is formed by the method of discrete interpolation (densification of points), which involves determining the position of intermediate points for the original point set. The rate of change of the radiuses of curvature of a discretely represented curve is estimated by the rate of change of the radiuses of curvature along the Bezier curve, which is determined by the basic triangle. The accuracy with which the value of the specified criterion represents the rate of change of the radiuses of curvature of a discretely represented curve depends on the size of the section bounded by two consecutive points of the curve: as the length of the section decreases, the value of the criterion approaches the desired value. A study of the properties of the Bezier curve was conducted, as a result of which it was proved that within the section along which the values of the radiuses of curvature change monotonically, the values of the criterion for evaluating the rate of change of the radii of curvature also change monotonically. A criterion for estimating the magnitude of the discontinuity of the rate of change of the radiuses of curvature of a discretely represented curve is proposed. The reduction of gaps in the criterion values is carried out in the process of condensation within the corresponding base triangle, as well as within the previous and subsequent triangles. In the process of successive thickenings, the maximum value of the gap in the values of the rate of change of the radii of curvature is successively reduced. In the case when the maximum value of the discontinuity does not exceed the specified value, a discrete curve is formed, along which the rate of change of the radii of curvature varies continuously. The application of the developed contour modeling method allows to improve the quality of the formation of functional surfaces of products when solving reverse engineering tasks, as well as when forming the surfaces of products that interact with the environment (blades of turbines, working bodies of agricultural machines, channels of internal combustion engines, etc.).
Development of the modeling algorithm of curves according to the given properties
Холодняк Ю. В., Гавриленко Є. А., Зінов’єва О. Г. Розробка алгоритму моделювання кривих з заданими властивостями. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Запоріжжя : ТДАТУ. 2023. Вип. 13, том 1. C. 476-491.
Keywords: алгоритм; каркас поверхні; обвід; диференціально- геометричні характеристики; кривина; algorithm; surface frame; outline; differential geometric characteristics; curvature